Exact solutions with generalized separation of variables for the nonlinear heat equation with a source - Barannyk, A.; Barannyk, T.; Yuryk, I. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.9 We propose a method for the construction of exact solutions to nonlinear heat-conduction equation with a source based on the classical method of separation of variables, its generalization, and the reduction method. We consider substitutions reducing the nonlinear heat-conduction equation to ordinary differential equations and to a system of two ordinary differential equations. The classes of exact solutions of the analyzed equation are constructed by the method of generalized separation of variables.